(untitled) (Nativa, 2023)
ABSTRACT: Adsorption is gaining attention by becoming one of the most used technologies for the removal of contaminants from water. Adsorption with activated charcoal (AC) is an efficient method for treatment of effluents; the main advantage of AC production is the use of residues that would be inappropriate discarded. The objective of this work was to gather and organize the information available about the potential of using activated charcoal as a bio-adsorbent. Researches were conducted on scientific articles about the production of activated charcoal with adsorption characteristics for the removal of contaminants from residual waters. The efficiency of this technique is dependent on different parameters that affect the adsorption process, such as: pH of the solution, dye initial concentration, contact time, adsorbent amount, and temperature. The articles studied showed that the bio-adsorbent characteristics of charcoals are promising for the removal of pollutants from residual waters. The isotherm adsorption models developed by Langmuir, Freundlich, and Brunauer, Emmett, and Teller (BET) are often used to evaluate the adsorption capacity of activated charcoals. Keywords: industrial effluents; contaminants; environmental management. Emprego do carvão ativado como bioadsorvente para o tratamento de águas residuais: uma revisão RESUMO: A adsorção vem ganhando destaque com uma das tecnologias mais empregadas na remoção de contaminantes em águas. No tratamento de efluentes, a adsorção com carvão ativado (CA) apresenta-se como um método eficiente. A principal vantagem da produção de CA é o aproveitamento de resíduos que seriam descartados de forma inadequada. O objetivo desta pesquisa é organizar algumas informações disponíveis com relação ao potencial do carvão ativado como bioadsorvente. Foram realizadas pesquisas em periódicos sobre produção de carvão ativado com características adsortivas na remoção de contaminantes em águas residuais. A eficácia dessa técnica sob diferentes parâmetros influencia no processo de adsorção, tais como: pH da solução, concentração inicial do corante, tempo de contato, quantidade do adsorvente e temperatura. Em todos os artigos estudados, as características dos carvões como bioadsorventes se mostraram promissores no processo para remoção de poluentes em águas residuais. Conclui-se que os modelos de isotermas de adsorção desenvolvidos por Langmuir, Freundlich e BET são frequentemente utilizados para avaliar a capacidade de adsorção dos carvões ativados. Palavras-chave: efluentes industriais; contaminantes; gestão ambiental.